Key HRDM factors enhancing SMEs’ performance - Havierniková, Katarína; Hunková, Lukrécia; Skačkauskienė, Ilona; Navickas, Valentinas (Journal of Business Economics and Management, 2025)
The impact of human resources development (HRD) on business performance is critical for enterprises, but there’s limited analysis of the specific factors affecting small and medium-sized enterprises (SMEs) in terms of human resources development management (HRDM). This paper aims to identify the key HRDM factors influencing SMEs’ performance from two perspectives: individual employee development and organizational development. It also categorizes entrepreneurs based on these factors. Exploratory factor analysis (EFA) and cluster analysis using the K-means method were applied in analysis of data from SMEs. For individual development, three factors were identified: Development practices, career growth, and rewards systems. Based on these, SMEs were grouped into three clusters: career and rewards-focused SMEs, development and career-oriented SMEs, and development-focused SMEs. Career Growth was found to have the greatest impact on performance. For organizational development, three factors emerged: Training, Talent Development, and Work Systems. Analysis yielded three clusters: training and work systems-focused SMEs, talent development-focused SMEs, and work systems-focused SMEs, with training being the most influential for organizational performance. The study highlights the importance of HRDM strategies for different groups of SMEs to enhance performance and deepen the understanding of HRDM’s role in SMEs, showing the complex relationships between these factors and overall firm success.